Effects of sorghum starch type, endosperm hardness, and processing on digestibility and growth performance in finishing pigs and chicks - H Cao; Robert H Hines; B W Senne; J R Froetschner; J M Jiang; S L Johnston; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1998)
In finishing pigs, waxy sorghum had lower digestibilities for DM and GE than the other genotypes. Also, the hard sorghums were more digestible (P<.06) than the medium hardness sorghum. In broiler chicks, the waxy sorghum was similar to the other genotypes for growth performance and nutrient digestibility. The soft sorghum was superior to the medium and hard genotypes for nutrient retention but not for growth performance. Fine grinding improved F/G and increased retention of nutrients and steam-flaked sorghum supported greater growth performance than extruded sorghum.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Sorghum; Processing; Chicks; Finishing pigs